Výroba řetězového kolečka BMX kola - Figar, Erik (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Prace se zabyva navrhem vhodne technologie pro vyrobu retezoveho kolecka BMX kola, vyrobeneho z plechu 14 220.3, o tloustce 4 mm. Vyrobni serie cini 200 000 kusu za rok. Po analyze ruznych moznosti vyroby byla zvolena jako nejvhodnejsi technologie presneho strihani s tlacnou hranou. Byl vytvoren technologicky navrh, jenz zahrnuje volbu vhodneho polotovaru (tabule plechu 4x2000x6000 mm), navrh strizneho nastroje s prislusnou vykresovou dokumentaci vybranych dilcu. Na zaklade vypoctenych hodnot byl dale zvolen vyrobni stroj, hydraulicky trojcinny lis HFA 4500 plus od firmy Feintool. V posledni fazi bylo provedeno technicko-ekonomicke zhodnoceni efektivnosti teto vyroby.

The thesis deals with the design of suitable technology for the production of BMX sprocket made of sheet metal 14 220.3, with a thickness of 4 mm. The production series is 200,000 units per year. Following the analysis of different production options, fine-blanking technology has been chosen as the most suitable precision cutting technology. A technological proposal has been created, which includes the choice of a suitable appropriate blank (sheet metal 4x2000x6000 mm) as well as the design of a shearing tool with the corresponding drawing documentation of its selected parts. On the basis of the calculated values, HFA 4500 plus hydraulic triple action press manufactured by the Feintool company was selected as a production machine. In the last stage, technical and economic assessment of the efficiency of this production was performed.
Manufacturing of chain wheel for BMX bike
Keywords: Plosne tvareni; retezove kolecko; strizny nastroj; ocel 14 220.3; presne strihani; tlacna hrana; sheet metal forming; chain wheel; shearing tool; steel 14 220.3; fine blanking; vee-shaped ring